1988
DOI: 10.1172/jci113771
|View full text |Cite
|
Sign up to set email alerts
|

Role of intracellular sodium in the regulation of intracellular calcium and contractility. Effects of DPI 201-106 on excitation-contraction coupling in human ventricular myocardium.

Abstract: Experiments were performed to investigate the mechanism of action of DPI 201-106 on human heart muscle. In both control and myopathic muscles, DPI produced concentration-dependent increases in action potential duration, resting muscle tension, peak isometric tension, and duration of isometric tension. These changes were associated with increases in resting intracellular calcium and peak calcium transients as measured by aequorin. At higher concentrations of DPI, a second delayed Ca2l transient (L') appeared. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It is only at higher stimulus frequencies that depressed myocardial contractility is observed and peak intracellular calcium concentration is reduced in the presence of elevated diastolic calcium concentrations (Schmidt et al 1998). We have also shown that at higher stimulus frequencies with failing human myocardium, there is progressive abbreviation in APD as opposed to the abbreviation seen in non-failing myocardium that stabilizes at a set frequency and APD (Gwathmey et al 1988). Similarly, we found that APD was dynamically changed in response to stimulus frequency perturbation in failed avian myocardium, such that APD did not reach steady-state at higher frequencies.…”
Section: Discussionmentioning
confidence: 55%
“…It is only at higher stimulus frequencies that depressed myocardial contractility is observed and peak intracellular calcium concentration is reduced in the presence of elevated diastolic calcium concentrations (Schmidt et al 1998). We have also shown that at higher stimulus frequencies with failing human myocardium, there is progressive abbreviation in APD as opposed to the abbreviation seen in non-failing myocardium that stabilizes at a set frequency and APD (Gwathmey et al 1988). Similarly, we found that APD was dynamically changed in response to stimulus frequency perturbation in failed avian myocardium, such that APD did not reach steady-state at higher frequencies.…”
Section: Discussionmentioning
confidence: 55%
“…However, this pathway can also promote Ca 2 + influx. Ca 2 + influx would continue during the plateau phase of the action potential until membrane potential repolarizes to −40 mV, the calculated reversal potential for Na + -Ca 2 + exchange [43]. At that point Ca 2 + efflux would begin, resulting in relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the Na +-Ca 2 + exchanger to Ca 2 + handling could be more efficient in HF if one takes into account that messenger RNA (mRNA) as well as protein levels are significantly increased in the failing human heart [9,44]. Another potential source of Ca 2 + entry during action potential plateau, the L-type Ca 2 + ''window'' current [45], was shown to have a limited contribution to overall Ca 2 + entry into the cell in human HF [43]. The data on L-type Ca 2 + -channel expression in HF are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…1 (top (12). The action potential was also prolonged ( 14,15 ). The addition of 1 X lo-5 M ryanodine significantly depressed the peak levels of tension and Ca?'.…”
Section: Resultsmentioning
confidence: 95%
“…The (12,14,15). With this combination of drugs, Ca2" release from the sarcoplasmic reticulum (SR), which predominantly regulates the Ca?'…”
Section: Methodsmentioning
confidence: 99%